Factors affecting brand loyalty in Malaysia retail industry - Goh, Qian Feng (2023)
This research adopts the brand loyalty theory to determine the major factors (customer service,convenience, price, and perceived quality) that can affect the brand loyalty in Malaysia retail industry. Moreover, this research can help the domestic retailer improve their retailmanagement in order to enhance their overall sales revenue and service quality.